Are Asset Price Guarantees Useful for Preventing Sudden Stops?A Quantitative Investigation of the Globalization Hazard-Moral Hazard Tradeoff - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 2006)
An implication of the "globalization hazard" hypothesis is that sudden stops could be prevented by offering foreign investors price guarantees on emerging markets assets. These guarantees create a tradeoff, however, because they weaken globalization hazard by creating international moral hazard. We study this tradeoff using an equilibrium asset-pricing model. Without guarantees, margin calls and trading costs cause Sudden Stops driven by Fisher's debt-deflation process. Price guarantees prevent this deflation by propping up foreign asset demand, but their effectiveness and welfare implications depend critically on the price elasticity of foreign demand and on making the guarantees contingent on debt levels.